2022
DOI: 10.3390/foods11101395
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Signatures Associated with Peanut Allergy in a BALB/c Mouse Model

Abstract: Multiple studies have uncovered the pivotal role of gut microbiota in the development of food allergy. However, the effects of gut microbiota on peanut allergy are still unclear. Here, we characterized the gut microbiota composition of peanut-allergic mice by 16S rRNA sequencing and analyzed the correlation between allergic indicators and gut microbiota composition. Outcomes showed that the gut microbiota composition was reshaped in peanut-allergic mice, with Acidobacteriota, Lachnospiraceae, Rikenellaceae, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
5
12
0
Order By: Relevance
“…62 It has also been discovered that the relative abundance of Acidobacteriota and Lachnospiraceae was reduced in the intestine of peanut-allergic mice. 63 This study found a remarkable decline in the proportion of Firmicutes in OVA-sensitized mice, which was consistent with previous findings. 20 There was also a noticeable increase in the relative abundance of Desulfobacterota .…”
Section: Discussionsupporting
confidence: 93%
“…62 It has also been discovered that the relative abundance of Acidobacteriota and Lachnospiraceae was reduced in the intestine of peanut-allergic mice. 63 This study found a remarkable decline in the proportion of Firmicutes in OVA-sensitized mice, which was consistent with previous findings. 20 There was also a noticeable increase in the relative abundance of Desulfobacterota .…”
Section: Discussionsupporting
confidence: 93%
“…63,64 In agreement with our results, Rachid et al 65 reported that there was increased relative abundance of Bacteroidetes and reduced relative abundances of Firmicutes and Proteobacteria in food-allergic infants. The relative abundance of Acidobacteriota was remarkably decreased in peanut-induced allergic mice, 22 which was consistent with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…63,64 In agreement with our results, Rachid et al 65 reported that there was increased relative abundance of Bacteroidetes and reduced relative abundances of Firmicutes and Proteobacteria in food-allergic infants. The relative abundance of Acidobacteriota was remarkably decreased in peanut-induced allergic mice, 22 which was consistent with our observations. LEfSe analysis illustrated that at the genus level, upregulated relative abundances of Bacteroides, Lactobacillus, Parabacteroides, Alloprevotella and Helicobacter were observed in the HS group.…”
Section: Papersupporting
confidence: 91%
See 2 more Smart Citations